Development of Healthy Shallot Herbal Tea (Allium ascalonicum L.) with Antioxidant Activities - Musika, Jirayu; Musika, Thanawan (Journal of Food Technology, Siam University, 2021)
This research aimed to develop the healthy herbal tea product from shallots (Allium ascalonicum L.) by creating product concepts from focus group of 20 consumers who like to drink tea (40–65 years old) in Sisaket Province (N=20). It was found that 80% of customers wanted to add value of healthy herbal tea with shallots which was clear, fragrant and a unique local product. The tea formula was developed and optimized by using mixture design, main ingredients of the herbal tea were shallots, while pandan leaves and shallot leaves were tea flavoring agents and response surface methodology (RSM), respectively. Antioxidant activities, physicochemical properties and sensory evaluation of 6 herbal tea formula were compared. The results showed that an increase in shallot leaves and pandan leaves could enhance the brightness (L*), antioxidant activities by using DPPH and ABTS, and sensory scores. The optimal formula ratio of shallots, pandan leaves and shallot leaves analyzed by RSM (R2>0.75) were 45%, 35% and 20%, respectively. The consumer acceptance for shallot herbal tea was tested. The overall liking scores and product acceptance were 7.03 and 98%, respectively. More than 90 % of customers decided to buy this product at a price of THB 100/20 grams.